Effects of glycyrrhizin on the pharmacokinetics of nobiletin in rats and its potential mechanism - Hao Wang; Lin Dong; Fangfei Qu; Huimin He; Wei Sun; Yuqing Man; Hongjie Jiang (Taylor & Francis Group, 2020)
Context Both nobiletin (NBL) and glycyrrhizin (GL) have anti-inflammatory and antitumor properties. These agents may be co-administered in the clinic. However, the drug-drug interaction between them is not clear. Objective The drug-drug interaction between GL and NBL was investigated, to clarify the effect of GL on the pharmacokinetics of NBL, and its main mechanism. Materials and methods The pharmacokinetic profiles of oral administration of NBL (50 mg/kg) in Sprague-Dawley rats of two groups with six each, with or without pre-treatment of GL (100 mg/kg/day for 7 days), were investigated. The effects of GL on the metabolic stability and transport of NBL were also investigated through the rat liver microsome and Caco-2 cell transwell models. Results The results showed that GL significantly decreased the peak plasma concentration (from 1.74 ± 0.15 to 1.12 ± 0.10 μg/mL) and the t1/2 (7.44 ± 0.65 vs. 5.92 ± 0.68) of NBL, and the intrinsic clearance rate of NBL was increased by the pre-treatment with GL (39.49 ± 2.5 vs. 48.29 ± 3.4 μL/min/mg protein). The Caco-2 cell transwell experiments indicated that GL could increase the efflux ratio of NBL from 1.61 to 2.41. Discussion and conclusion These results indicated that GL could change the pharmacokinetic profile of NBL, via increasing the metabolism and efflux of NBL in rats. It also suggested that the dose of NBL should be adjusted when co-administrated with GL in the clinic.